Synthesis of 5-R-4-R1-3-alkylthio-1,2,4-triazoles and study influence of their adsorption ability on the results of toxicity and anti-hypoxic activity - Kucheryavyi, Yu. M.; Kaplaushenko, A. G.; Korzhova, A. S.; Кучерявий, Юрій Миколайович; Каплаушенко, Андрій Григорович; Коржова, Алла Станіславівна (My University, 2014)
During our research of biologically active substances we have synthesized series of new 5-R-4-R1-3-alkylthio-1,2,4- triazoles for original drugs creation. 14 new compounds have been synthesized in total. The structure of it has been confirmed by a complex of modern physical and chemical methods of analysis. For these compounds the data of toxicity, anti-hypoxic activity, surface activity and adsorption ability has been set. The obtained results of biological activity have been compared with data of adsorption properties of 1,2,4-triazoles derivatives to establish structureaction regularity.
Keywords: 1,2,4-triazoles; physical and chemical properties; susceptibility to adsorption; toxicity; anti-hypoxic activity